2021
DOI: 10.1017/s1368980021004535
|View full text |Cite
|
Sign up to set email alerts
|

Impact of front-of-pack labels on the perceived healthfulness of a sweetened fruit drink: a randomised experiment in five countries

Abstract: Objective: Front-of-pack (FOP) nutrition labelling is a globally recommended strategy to encourage healthier food choices. We evaluated the effect of FOP labels on the perceived healthfulness of a sweetened fruit drink in an international sample of adult consumers. Design: Six-arm randomised controlled experiment to examine the impact of FOP labels (no label control, Guideline Daily Amounts (GDA), Multiple Traffic Lights, the Health Star Ratings (HSR), Health Warning Labels, and ‘High-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This information is expected to require more time and cognitive effort to interpret compared with the OWL or MGG, as reported in previous studies based on response times 43 49. Previous studies have also shown that the use of green colour found in systems such as the TFL and Nutri-Score may drive consumers to misperceive a product as healthier and undesirably raise their appetite for such products, which may explain their lower effect on understanding of nutritional information and purchase intention 49 51–61. In addition, the use of red colour, also found in such systems, although intended to communicate a higher harmfulness level, may trigger an opposite effect in some products.…”
Section: Discussionmentioning
confidence: 90%
“…This information is expected to require more time and cognitive effort to interpret compared with the OWL or MGG, as reported in previous studies based on response times 43 49. Previous studies have also shown that the use of green colour found in systems such as the TFL and Nutri-Score may drive consumers to misperceive a product as healthier and undesirably raise their appetite for such products, which may explain their lower effect on understanding of nutritional information and purchase intention 49 51–61. In addition, the use of red colour, also found in such systems, although intended to communicate a higher harmfulness level, may trigger an opposite effect in some products.…”
Section: Discussionmentioning
confidence: 90%
“…Among adults, sweetener disclaimers led to a lower perceived healthfulness of the sugary drink among older compared with younger participants. Similarly, a larger effect of warning labels on the perceived healthfulness ratings of a sugary drink was observed among older adults than younger adults from the UK (34) . It has been stated that older adults have greater health risk perceptions (how individuals subjectively estimate and feel about the risks they face) compared with their younger counterparts (35,36) .…”
Section: Discussionmentioning
confidence: 98%
“…UK consumers utilise the information on the FOP and BOP nutrition labels during food shopping to monitor what they will purchase (Kelly & Jewell, 2019; Department of Health and Social Care (DHSC), 2020; Bhawra et al ., 2022). This is the same in the United States, Australia and elsewhere (Dickie et al ., 2018; Jones et al ., 2019; Jáuregui et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%